Impact of the COVID-19 pandemic on midwifery-led service provision in the United Kingdom in 2020-21: findings of three national surveys - Brigante, L; Morelli, A; Jokinen, M; Plachcinski, R; Rowe, R (Elsevier, 2022)
Background The COVID-19 pandemic required all healthcare systems to adapt quickly. There is some evidence about the impact of the pandemic on United Kingdom maternity services overall, but little is known about the impact on midwifery-led services, including midwifery units and home birth services.